Estudo da influência de variáveis de composição e processamento nas propriedades de corpos cerâmicos porosos obtidos a partir do resíduo do polimento do porcelanato - Menezes, Raquel Rodrigues do Nascimento (2021)
The study of industrial waste has become commonplace in the scientific environment, due to the inadequate disposal of these materials, generating harm to the environment and the population. Among these residues, the porcelain tile polishing residue (RPP) gains prominence, due to the large scale of porcelain tile manufacturing and its high potential for reuse. This work aimed to evaluate processing variables in the technological properties of ceramic bodies based on PPR, for this purpose, an experimental factorial planning 23 was carried out with repetitions at the central point, varying feldspar content added to the PPR (0, 3 and 6%), different conformation pressures (40, 50 and 60 MPa) and firing temperatures (1120, 1150 and 1180°C). The raw materials were characterized by X-ray diffraction, X-ray fluorescence, particle size analysis and thermal analysis. The technological properties of the ceramic bodies produced were evaluated by statistical analysis of the data and methodology of response surfaces, in addition to morphological analysis by scanning electron microscopy. The characterization results indicated that the raw materials presented characteristics similar to those presented in other scientific studies, with emphasis on the PPR which has a complex chemical and mineralogical composition, since it is usually composed of the formulation of porcelain tile and abrasive materials from the polishing machine. In this residue, the presence of silicon carbide (SiC) was detected, which, under specific conditions of temperature and composition, suffers thermal reactions promoting the formation of high amount of pores inside the ceramic pieces. The most influential factor, in all the properties studied, was the firing temperature, which when increased from 1120ºC to 1180ºC, promoted an average increase of about 150.16% in volumetric expansion, an average increase of about 34.94% in porosity and an average reduction of about 3.06 MPa in the mechanical resistance of the ceramic bodies. The analysis of the response surfaces showed that the regions containing maximum values of volumetric expansion (ranging from 180% to 220%) and porosity (ranging from 60% to 70%) are located at temperatures ranging from 1165ºC to 1180ºC. The regions with maximum values of resistance to traction by diametrical compression (ranging from 5 to 6 MPa) are located at temperatures below 1140ºC, approximately. In general, the study presents a range of information that is of paramount importance for the use of PPR residues in the production of highly porous ceramic bodies.